2005
DOI: 10.1002/elps.200410153
|View full text |Cite
|
Sign up to set email alerts
|

The zeta potential of cyclo-olefin polymer microchannels and its effects on insulative (electrodeless) dielectrophoresis particle trapping devices

Abstract: While cyclo-olefin polymer microchannels have the potential to improve both the optical detection sensitivity and the chemical resistance of polymer microanalytical systems, their surface properties are to date not thoroughly characterized. These surface properties dictate, among other things, electrokinetic effects when electric fields are present. Here, we report the measurement of the zeta potential of cyclo-olefin polymers (injection-molded and hot-embossed Zeonor 1060R and 1020R) microchannels as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 22 publications
5
88
0
Order By: Relevance
“…In the improved method a general least-square analysis is used to account for measurement uncertainties. Mela et al [12] used the streaming potential method to measure the zeta potential for characterizing the cyclo-olefin polymer microchannels. Sze et al [13] used the current monitoring method [14] to determine the zeta potentials of channel surfaces by using the Smoluchowski equation together with the measured slope of current-time relationship in EOFs.…”
Section: General Aspectsmentioning
confidence: 99%
“…In the improved method a general least-square analysis is used to account for measurement uncertainties. Mela et al [12] used the streaming potential method to measure the zeta potential for characterizing the cyclo-olefin polymer microchannels. Sze et al [13] used the current monitoring method [14] to determine the zeta potentials of channel surfaces by using the Smoluchowski equation together with the measured slope of current-time relationship in EOFs.…”
Section: General Aspectsmentioning
confidence: 99%
“…The iDEP chip has been employed to selectively trap and concentrate both live and dead E. coli and separate different species of live bacterial cells from water School of Nano-Biotechnology and Chemical Engineering, UNIST, Ulsan, Republic of Korea using a direct current electric field [7,12,13,19]. Mela et al, reported reduced trapping voltage thresholds for the iDEP chips fabricated with cyclo-olefin polymer as compared with the previously reported glass-based iDEP chips [22].…”
Section: Introductionmentioning
confidence: 98%
“…In iDEP chips, the DEP trap is formed by geometrical constrictions in insulating substrates (e.g. quartz [6,7,12,13,18], glass beads [20,24], cyclo-olefin polymer [22], PMMA [21], and polycarbonate (PC) [23]) instead of metallic microelectrodes. A Nonuniform electric field is generated near the non-uniform structures made of insulating materials when an electric field is applied to remotely located electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymers such as poly(methylmethacrylate) (PMMA) [4], PDMS [5], polycarbonate (PC) [6], polyester [7], and poly(ethylenterephthalate) (PET) [8] have been employed. Recently, cyclic olefin polymers and copolymers such as Zeonor [9] or thermoplastic olefin polymer of amorphous structure (Topas) [10] have also received attention due to their high chemical resistance, good machinability, and optical transparency.…”
Section: Introductionmentioning
confidence: 99%